The Relationship between Birth Weight, Birth Height, and Dental Development by Demirjian's Method - Najmeh Anbiaee; Anousheh Rashed Mohassel; Shakiba Afzalinasab (Mashhad University of Medical Sciences, 2013)
Introduction: Like other measures of human development, dental development is not in complete accordance to chronological age. Investigations show that dental age can be affected by gender, race, systemic conditions, and some other factors and consequently, be different in people of the same chronological age. A correct estimation of dental age and its development in children is of great importance to design the appropriate dental treatment plan. One of the factors predicted to influence dental development is the physical status of newborn, of which, the most common indices are birth weight and height. The aim of this study was to evaluate the effects of these two factors on the dental development of permanent teeth in children of both genders. Methods: The dental ages of 211 of 4-14 year old healthy children were calculated using their panoramic radiographs according to Demirjian's method. Birth weight, height, and date were recorded from the vaccination certificate. The dental development rate was obtained by subtracting chronological age from dental age. Pearson correlation tests and regression analysis were conducted in both genders. Results: the correlation between dental development and birth weight and birth height was positive, when separated by gender; this correlation was only significant among females. Conclusion: There is a positive relationship between physical status of newborn and the development of permanent teeth. This should be taken into consideration when designing dental treatment plans for children